2016
DOI: 10.1080/21501203.2016.1168885
|View full text |Cite
|
Sign up to set email alerts
|

Does elevation influence the distributional patterns of tropical myxomycetes? A case study in Costa Rica

Abstract: In order to test the hypothesis that elevation may be an important factor accounting for the distribution of myxomycetes in tropical forests, this project was designed and conducted in Costa Rica. Two lower elevational belts were selected for this work due to their floristic and structural resemblance. Using the moist chamber technique, 40 different sites located in four different transects in two different macroclimatic regions were surveyed using three substrates during the rainy and the dry periods of 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Such an observation has already been made in other studies in tropical areas (Ogata et al 1996, Ko Ko et al 2011 and have been suggested to be the general pattern in the tropics (Novozhilov et al 2017). Some investigations in Costa Rica comparing wet-dry tropical forests (Rojas & Valverde 2015) and seasonal dynamics (Rojas et al 2016) show the opposite pattern but using data from different recording techniques. In general, myxomycetes can clearly thrive over a wide range of conditions (Estrada-Torres et al 2009) and too much precipitation can affect the integrity of sporocarps, but the results presented herein support the idea that wet substrates during the rainy months are more favorable for most species to produce sporocarps under tropical conditions.…”
Section: Tubifera Microsperma 9supporting
confidence: 62%
“…Such an observation has already been made in other studies in tropical areas (Ogata et al 1996, Ko Ko et al 2011 and have been suggested to be the general pattern in the tropics (Novozhilov et al 2017). Some investigations in Costa Rica comparing wet-dry tropical forests (Rojas & Valverde 2015) and seasonal dynamics (Rojas et al 2016) show the opposite pattern but using data from different recording techniques. In general, myxomycetes can clearly thrive over a wide range of conditions (Estrada-Torres et al 2009) and too much precipitation can affect the integrity of sporocarps, but the results presented herein support the idea that wet substrates during the rainy months are more favorable for most species to produce sporocarps under tropical conditions.…”
Section: Tubifera Microsperma 9supporting
confidence: 62%
“…In constantly wet highland forests, myxomycetes seemed to utilize aerial litter, which dries out faster, more often than ground microhabitats Lado et al, 2003Lado et al, , 2017. Therefore, the moisture regime, not elevation per se may be the driver of differences in the abundance of fruiting bodies (Rojas et al, 2016).…”
Section: Differences In Species Abundances and Composition Between Thmentioning
confidence: 99%